Criminal Liability For Placement Actors Illegal Female Labor - Ibrahim Nainggolan (Eduvest - Journal of Universal Studies, 2021)
The distribution of Indonesian workers carried out by individuals, not by the government or by official private companies distributing Indonesian workers, still occurs. The placement of workers in Indonesia abroad needs to be carried out in an integrated manner between government agencies, both central and regional and the participation of the community in a adequate legal products to provide maximum protection. The state is obliged to guarantee and protect the human rights of its citizens who work both at home and abroad based on the principles of equal rights, democracy, justice, social, gender equality, and anti-discrimination. know the criminal responsibility for individual perpetrators who participate in the placement of illegal female workers to Malaysia. This research is a normative legal research taken from secondary data in the form of library research. Based on the results of the study, it is understood that legal arrangements regarding legal practice have not been able to explain the doctrine of participating in criminal acts. On the one hand, participating in doing so is equated with acts together so that it does not distinguish between participating in committing as a form of participation and criminal acts in general. The target of the placement of workers is directed at placing workers in the right positions according to their expertise, skills, talents, interests and abilities by taking into account the dignity, rights, and legal protection.